Plerixafor (Mozobil) for stem cell mobilization in patients with multiple myeloma previously treated with lenalidomide - Micallef, Ivana N.; Ho, Anthony Dick; Klein, L. M.; Marulkar, S.; Gandhi, P. J.; McSweeney, P. A. (Bone marrow transplantation, 2011)
Lenalidomide and other new agents have considerable activity in multiple myeloma (MM) and have changed the landscape of treatment. Data suggest that lenalidomide therapy before autologous hematopoietic stem cell transplantation has a detrimental effect on stem cell mobilization. This retrospective study examined the efficacy of plerixafor in combination with G-CSF among patients with MM previously treated with lenalidomide (median, 4 cycles; range, 1-20 cycles). Data were analyzed for 60 patients who received plerixafor plus G-CSF for frontline mobilization in a phase 3 clinical trial or an expanded access program (n=20) or for remobilization in a compassionate use program (n=40). The overall median number of CD34+ cells collected was 5.6 × 106 per kg (range, 0.45 × 106-37.2 × 106). The minimum number of CD34+ cells (⩾2 × 106 per kg) was collected from 86.7% of patients in a median of 1 day. This minimum was collected from 100% of patients who underwent frontline mobilization and 80% of patients who underwent remobilization. These data suggest that CD34+ hematopoietic stem cells can be successfully and predictably collected with combination plerixafor plus G-CSF for primary or secondary mobilization in the majority of patients with MM who have been previously treated with lenalidomide.
published online 17 May 2010
Gesehen am 19.08.2022